Dampak judi online di ruang publik dan domestik - Maryam, Ayu Siti (Maliki Interdisciplinary Journal, 2025)
The rise of online gambling in Indonesia is a major issue that must be studied properly and wisely. Online gambling can be done by anyone regardless of time and place. This article aims to analyze the impact of online gambling in public and domestic spaces. This study also aims to prevent online gambling in the Indonesian community. By using a literature review approach, it is hoped that this article can provide deeper insight into the issue of online gambling and encourage efforts to create a better and wiser society in using technology. The results of the study show that online gambling has become a common thing done by people, both men and women, to get money quickly and double their money. The impact of online gambling is not only on oneself but also on other people and their families, even to the point of destroying a family.